Fine-ware from Hadrianopolis: from Hellenistic Village to Roman Vicus - Perna, Roberto; Capponi, Chiara; Cingolani, Sofia (Rei Cretariae Romanae Fautorum Acta, 2015)
Since 2005 the University of Macerata and the Archaeological Institute of Tirana have cooperated in the first archaeological excavations of the Roman settlement of Hadrianopolis, near the modern village of Sofratikë. The town, in northern Epirus, lies in the broadest section of the valley of the river Drin, in Chaonia.